(untitled) (IAHS Medical Journal, 2023)
Background: Congenital Adrenal Hyperplasia (CAH) in children varies in presentation and progression with several challenges in optimal management. Effective treatment is to achieve normal growth and development while avoiding adrenal crisis and hyperandrogenisation though achieving the balance between over treatment and undertreatment remains challenging. Case Presentation: A 24 days old male child presented with repeated vomiting, severe weight loss and had decreased level of activity since 7 days of age. After total clinical, radiological, pathological evaluation it was diagnosed as congenital adrenal hyperplasia. Conclusion: The approach to its diagnosis and management was a combined multidisciplinary effort of the Departments of Pediatrics, Endocrinology and Pathology. IAHS Medical Journal Vol 5(2), Dec 2022; 70-73